EFFECT OF SPINAL MANIPULATION ON POSTURAL INSTABILITY IN PATIENTS WITH NON SPECIFIC LOW BACK PAIN - KANCHAN KUMAR SARKER,; UMASANKAR MOHANTY,; JASOBANTA SETHI, (International Journal of Pharma and Bio Sciences, 2016)
Nonspecific back pain is common, disabling, and costly. Therefore, we assessed effectiveness of spinal manipulation (OMT) in the management of nonspecific low back pain (LBP) regarding postural instability (PI), pain pressure threshold (PPT) and pain intensity. The purpose of this paper is to describe the methodology of an experimental clinical trial examining the effectiveness of spinal manipulative in patients with non specific low back pain. 70 participants with non specific low back pain were distributed in two groups. 1st Group was treated with spinal manipulation high velocity low amplitude (HVLA) thrust where 2nd Group treated with Core stability exercises and both groups received common ergonomic advices. The outcome measures were checked with postural instability using win track software and platform, pressure pain threshold by digital algometer and pain intensity by numeric pain rating scale. Both groups have shown after fifteen days improvement where as significant improvement has been seen in group 1st compared to group 2nd. The present clinical study indicates that spinal manipulation which was more effective than core stability exercises in reducing postural instability, pain intensity and increasing pressure pain threshold in patients with non specific low back pain.